2017
DOI: 10.1182/blood-2016-09-740209
|View full text |Cite
|
Sign up to set email alerts
|

miR-155 promotes FLT3-ITD–induced myeloproliferative disease through inhibition of the interferon response

Abstract: • miR-155 promotes myeloproliferation in the bone marrow, spleen, and blood of mice carrying the FLT3-ITD mutation.• miR-155 suppresses the IFN response in FLT3-ITD

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 36 publications
3
45
0
Order By: Relevance
“…97 This was in contrast to miR-155 high levels (.10fold above control), in which miR-155 acted as a tumor suppressor by repressing colony formation and proliferation, establishing a dosedependent effect of miR-155 in these AML mouse models. The study did confirm that the intermediate miR-155 expression levels were a better representation of what was seen in their pediatric AML data set (increased ;oneto sevenfold), values that were consistent with miR-155 expression in other AML data sets, 12,45 suggesting that miR-155 likely has a predominately oncogenic effect in human AML. The study highlights the importance of considering the level of expression in various model systems when studying miRNAs in AML.…”
Section: Varying Levels Of Mirna Expression May Have Opposing Effectsmentioning
confidence: 60%
See 1 more Smart Citation
“…97 This was in contrast to miR-155 high levels (.10fold above control), in which miR-155 acted as a tumor suppressor by repressing colony formation and proliferation, establishing a dosedependent effect of miR-155 in these AML mouse models. The study did confirm that the intermediate miR-155 expression levels were a better representation of what was seen in their pediatric AML data set (increased ;oneto sevenfold), values that were consistent with miR-155 expression in other AML data sets, 12,45 suggesting that miR-155 likely has a predominately oncogenic effect in human AML. The study highlights the importance of considering the level of expression in various model systems when studying miRNAs in AML.…”
Section: Varying Levels Of Mirna Expression May Have Opposing Effectsmentioning
confidence: 60%
“…miR-155 seems to have no phenotypic effect in MLL-rearranged AML, 44 but it is consistently found to play an oncogenic role in FLT3-ITD-driven AML pathogenesis. 42,45 miR-126 plays different roles and regulates different targets in normal vs malignant hematopoietic stem cells 35 and, interestingly, both overexpression and knockout of miR-126 promote leukemogenesis. 34 These studies highlight how the influence of an miRNA in AML can be dependent on the underlying genetic abnormalities that drive disease or cell type of expression.…”
Section: Improper Regulation Of Inflammatory Pathways Leads To Amlmentioning
confidence: 99%
“…In addition, researchers have found that miR-155-5p mediates T lymphocyte differentiation [26] and inhibits cell apoptosis [27]. In pathogenesis, miR-155-5p is associated with many diseases, such as cancer [28,29], cardiovascular disease [30], autoimmune disease [31], metabolic disease [32], and neurological disorders [33]. During HSV-1 infection, several studies have shown that the expression level of miR-155-5p is markedly increased by the viral infection [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Many genetic abnormalities linked to AML have been identified during the past few decades. 25 Among these abnormalities; the micro-RNA family has been given increased attention, especially over the past ten years. Clear evidence suggests that miRNAs play a role in many aspects of AML development, including maintenance of hematopoietic stem cells, growth, proliferation, differentiation, and apoptosis.…”
Section: Discussionmentioning
confidence: 99%